2017
DOI: 10.1016/j.cbpra.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Interviewing as an Adjunct to Cognitive Behavior Therapy for Anxiety Disorders: A Critical Review of the Literature

Abstract: Cognitive behavior therapy (CBT) is efficaciously and effectively used in the treatment of anxiety disorders; however, as CBT for anxiety routinely utilizes exposure components, clients often experience ambivalence about treatment and their clinicians often must deal with resistance. Motivational Interviewing (MI) is a therapeutic strategy that addresses ambivalence about change in clinical interventions. MI has been applied as an adjunct for treatments such as CBT in order to increase motivation for and commi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…MI is designed to explore and resolve ambivalence about behavioural change, and its effectiveness in the treatment of substance abuse is well known (Smedslund et al, 2011). A recent review found some improvement in treatment initiation and engagement following the addition of MI as an adjunct for CBT for anxiety disorders (Randall & McNeil, 2017). To date, MI approaches in PTSD have focused on ambivalence regarding changing PTSD symptoms or associated coping strategies in veterans (Murphy, Thompson, Murray, Rainey, & Uddo, 2009;Seal et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…MI is designed to explore and resolve ambivalence about behavioural change, and its effectiveness in the treatment of substance abuse is well known (Smedslund et al, 2011). A recent review found some improvement in treatment initiation and engagement following the addition of MI as an adjunct for CBT for anxiety disorders (Randall & McNeil, 2017). To date, MI approaches in PTSD have focused on ambivalence regarding changing PTSD symptoms or associated coping strategies in veterans (Murphy, Thompson, Murray, Rainey, & Uddo, 2009;Seal et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, client motivation, as assessed by self-report measures as well as by qualitatively coding client motivational language in session, is related to CBT outcomes and adherence (e.g., Bados et al, 2007 ; de Haan et al, 1997 ; Sijercic et al, 2016 ; Wergeland et al, 2005 ). Results from systematic reviews reveal MI enhances CBT response and completion rates for anxiety relative to CBT alone ( Ekelund, 2016 ; Randall and McNeil, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The second and third simulations focused on CBT with the second simulation targeting the introduction of CBT to a client, and the third simulation targeting the conducting of a CBT functional analysis. The authors chose simulations focused on MI and CBT because they are among the most versatile and empirically validated psychosocial treatments (Hofmann et al 2012;Randall and McNeil 2017). Moreover, the Brief MI and Introducing CBT simulations were recently examined and found to be efficacious (when delivered and evaluated under ideal research conditions) at enhancing clinical skills (Mastroleo et al 2020;Putney et al 2019a, b).…”
mentioning
confidence: 99%